Place identity: A theoretical reflection - Azmi, N.F.; Ahmad, F.; Ali, A.S. (Open House International Pub, 2014)
Each place possesses characteristics that confer on it a sense of place and identify through the meanings and values that they provide. The role of the physical built environment in place and identify development has not received adequate attention in built environment literature. This paper attempts to identify the unique and exceptional characteristics of places which create a unique environment and make a continuing contribution to the overall sense of the place. A preliminary survey was conducted in Kuala Kubu Bharu (KKB), a small town in the northern part of the Malaysian state of Selangor; to examine the characteristics of the place that influence and contribute to the identity of the town. The survey results demonstrate that the cultural heritage of the physical built environment acts as an important trigger for the town's identify. While it is undeniable that cultural heritage is indeed greatly the product of non-visual sources; subjective meanings, experiences, beliefs, ideology and past history of the place, this paper highlights the significance of the physical built environment in influencing the very individualiiy of the place.